Themochemical behaviour of empty fruit bunches and oil palm shell waste in a circulating fluidized-bed combustor (CFBC) - Hussain, Ahmad; Ani, Farid Nasir; Darus, Amer Nordin; Mokhtar, Hamdan; Azam, Saiful; Mustafa, Azeman (Palm Information Centre, Malaysian Palm Oil Board, 2006)

(untitled)
Circulatingfluidized-bed (CFB) technology is considered to be one of the most suitable techniques to thermally convertfuels into useful energy. However, practical experience is available for only a limited number of fuels and conditions. This paper describes the results from a bench-scale circulating fluidized-bed combustor (CFBC), installed at SIRIM Berhad, Shah Alam, for gasification and combustion of different biomass materials. The purpose of the tests was to investigate the suitabilify of the selected fuels for energy production using CFBC while taking care of the flue gas emissions. The experiments gave suficient information on the main process and flue gas characteristics. The measurements for temperatures and emissions were done for four dzferent biomass samples of empty fiuit bunch (EFB) of palm shell and palm shell waste powders of 2lO-3OO,425 and 600 microns. The concentrations of CO, NOx and CO, in the flue gas were measured continuously. The combustion performances were evaluated by varying the primary gas flow through the CFBC tubular furnace to identzfy the optimum operating conditions for the CFBC. The NOx content was from 20-164 ppm while the CO emissions were high for some operating conditions.